2014
DOI: 10.1007/s10584-014-1191-3
|View full text |Cite
|
Sign up to set email alerts
|

Near-term prediction of impact-relevant extreme temperature indices

Abstract: A previous study of predictability of European temperature indices revealed significant skill in predictions of 5/10-year average indices of summer mean and maximum 5-day average temperatures based on daily maximum and minimum temperatures for a large area of Europe, particularly in the Mediterranean. Here, this work is extended to study indices relevant to high heat-related impacts on energy use, human health and maize yields in Europe. The skill of predictions of these indices is assessed using decadal predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Prediction of extremely warm summers several years ahead could help in anticipating their occurrence and managing their impacts (e.g., Suarez-Gutierrez et al, 2018;Weisheimer et al, 2011). However, climate models struggle to skillfully predict warm summer temperature extremes on decadal time scales (e.g., Hanlon et al, 2013Hanlon et al, , 2014. Here, we examine the Coupled Model Intercomparison Project Phase 6 (CMIP6) version of the initialized Max Planck Institute Earth System Model (MPI-ESM-HR) and establish predictions of the probability with which warm summer temperature extremes in the Northern Hemisphere will occur.…”
Section: Introductionmentioning
confidence: 99%
“…Prediction of extremely warm summers several years ahead could help in anticipating their occurrence and managing their impacts (e.g., Suarez-Gutierrez et al, 2018;Weisheimer et al, 2011). However, climate models struggle to skillfully predict warm summer temperature extremes on decadal time scales (e.g., Hanlon et al, 2013Hanlon et al, , 2014. Here, we examine the Coupled Model Intercomparison Project Phase 6 (CMIP6) version of the initialized Max Planck Institute Earth System Model (MPI-ESM-HR) and establish predictions of the probability with which warm summer temperature extremes in the Northern Hemisphere will occur.…”
Section: Introductionmentioning
confidence: 99%
“…While significant progress has been made in analysing extreme events in seasonal predictions ( Hamilton et al, 2012 , Bhend et al, 2017 , Prodhomme et al, 2021 ) and climate projections ( Russo and Sterl, 2011 , Dosio, 2017 , Seneviratne and Hauser, 2020 ), much less attention has been given to the evaluation of extremes in decadal predictions. A few studies have recently assessed the skill of decadal predictions at predicting extreme heat stress, cold and wet rainfall events ( Eade et al, 2012 , Hanlon et al, 2015 , Solaraju-Murali et al, 2021 ). These studies generally found significant skill for extremes related to temperature and agreed that a substantial portion of that skill is linked to the long-term warming trend associated with the increase in anthropogenic greenhouse gases and aerosols, with the relative influence of natural variability and external forcings on forecast skill varying with the region considered.…”
Section: Discussionmentioning
confidence: 99%
“…Potential users of climate information are looking for the actual benefit that the skill information brings during their decision making process. While a number of studies have shown that decadal prediction can skillfully predict essential climate variables ( van Oldenborgh et al, 2012 , Corti et al, 2012 , Doblas-Reyes et al, 2013 ) and user-relevant indices ( Eade et al, 2012 , Hanlon et al, 2015 , Caron et al, 2015 , Paxian et al, 2019 , Solaraju-Murali et al, 2019 , Solaraju-Murali et al, 2021 ), it is still unclear what skill level is adequate for each user to confidently use such climate information for decision making. To address this, the coproduction effort, including ongoing conversations between the climate scientists and users and close collaboration, is required, in order, for example, to co-explore and define a suitable skill threshold.…”
Section: Discussionmentioning
confidence: 99%
“…The four papers in this special issue that present quantifications of different elements of the cascade of uncertainty were assessed in detail (Hanlon et al 2013;Otto et al 2003a;Saux Picart et al 2013;Watson et al 2014). The remaining four papers aim to inform uncertainty assessments by examining methodologies for assessment Lorenz et al 2013;Otto et al 2013b;Calel et al 2013).…”
Section: Experimental Design and Datamentioning
confidence: 99%
“…Hanlon et al (2013) (abbreviated to H2013) assess how well extreme heat events in the near future can be predicted using an ensemble of 9 climate model runs. They evaluate model skill through hind casting and then quantify some of the uncertainties through bootstrapping with replacement.…”
Section: Introductionmentioning
confidence: 99%